Outcomes of inflammatory bowel disease in patients with eosinophil-predominant colonic inflammation. Issue 1 (16th February 2020) - Alhmoud, Tarik; Gremida, Anas; Colom Steele, Diego; Fallahi, Imaneh; Tuqan, Wael; Nandy, Nina; Ismail, Mahmoud; Aburajab Altamimi, Barakat; Xiong, Meng-Jun; Kerwin, Audra; Martin, David
Abstract : Background: Inflammatory bowel disease (IBD) is characterised by acute intestinal mucosal inflammation with chronic inflammatory features. Various degrees of mucosal eosinophilia are present along with the typical acute (neutrophil-predominant) inflammation. The effect of intestinal eosinophils on IBD outcomes remains unclear. Methods: This is a retrospective study. Archived intestinal mucosal biopsy specimens of treatment-naïve IBD patients were examined by two pathologists. The number of eosinophils per high-power field was counted, and the mucosal inflammation was classified according to the eosinophilic inflammatory patterns. Clinical outcomes during the follow-up period were recorded. Results: 142 treatment-naïve IBD patients were included. Mean age was 39 years. 83% of patients had ulcerative colitis, and median follow-up was 3 years. 41% of patients had disease flare(s) and 24% required hospitalisation. Eosinophil count was not associated with risk of disease flare or hospitalisation. Patients with neutrophil-predominant inflammation (>70% neutrophils) had greater risk of disease flare(s): 27(55%) versus 24(36%) and 7(28%) in patients with mixed and eosinophil-predominant inflammation, respectively (p=0.04). Overall, patients with neutrophil-predominant inflammation were more likely to have a disease flare; HR: 2.49, 95% CI (1.0 to 5.6). Hospitalisation rate was higher in patients with neutrophil-predominant inflammation: 17(35%) compared to 17(19%) in patients with eosinophil-rich inflammation (p=0.04). Kaplan–Meier analysis showed higher flare-free survival in patients with eosinophil-predominant inflammation compared to mixed and neutrophil-predominant inflammation. Conclusion: IBD patients with eosinophil-predominant inflammation phenotype might have reduced risk of disease flares and hospitalisation. Larger prospective studies to assess IBD outcomes in this subpopulation are warranted.